Strategies Educational Service and Innovation of Learning Materials in Enhancing Cadet Satisfaction at the National Maritime Academy of Greater Jakarta - Kwartama, Agung; Paiman; As’ad, Abdul Rasyid; Abbas, Rianat; Ahmed, Abdal (Cendekiawan Indonesia Timur, 2025)
This research aims to explore the educational service strategies and innovative learning materials implemented at the National Maritime Academy of Greater Jakarta to enhance cadet satisfaction. The methodology employed in this study is a quantitative approach, with surveys serving as the data collection instrument. The research sample consists of 90 cadets selected randomly. The collected data were analysed using descriptive and inferential statistical techniques. The results indicate a significant positive relationship between effective educational service strategies and innovative learning materials and the level of cadet satisfaction. For instance, 85% of respondents stated that innovations in learning materials, such as the use of digital technology, greatly assist in understanding course content. Furthermore, responsive and communicative service from lecturers also contributes to cadet satisfaction, with 78% of cadets expressing satisfaction with their interactions with instructors. These findings suggest that enhancing educational service strategies and innovating learning materials could be key to improving cadet satisfaction at the National Maritime Academy of Greater Jakarta.